Global connectedness in higher education: student voices on the value of cross-cultural learning dialogue. Issue 11 (1st November 2016) - Lehtomäki, Elina; Moate, Josephine; Posti-Ahokas, Hanna
Abstract : The study explores how sense of global connectedness can be enhanced by creating opportunities for cross-cultural dialogue in higher education. Thematic analysis of randomly selected 15 learning journals, students' reflections on their learning during an international seminar was used to identify students' significant learning experiences. The results emphasise the added value of diversity (geographical, disciplinary, cultural and social) among students, faculty and invited presenters for creating meaningful learning. Furthermore, they suggest that designing an integrated approach of contents, contexts and activities for critical engagement in global dialogue and knowledge generation in higher education can open up new perspectives to students in education and thereby increase their sense of global connectedness. The research addresses internationalisation of higher education, contributes to the development of international study programmes and provides means to enhance inclusion of global issues in higher education policies, curricula and practice.